The Effect of Mobile Banking Services on Banking Performance with the Mediating Role of Customer Intention: A Case of Selected Commercial Banks in Borena, Southern Ethiopia - Achalu Teshome; Mohammed Arshad; Berhanu Borji (Winaya Inspirasi Nusantara Foundation, 2025)
Background of the problem: The effect of Mobile banking services on banking performance with the mediating role of customer intention. Purpose: to provide a better understanding of the effect of mobile banking services on bank performance in selected banking sectors of Ethiopia from a mediating role customers’ intention perspective. Method: a mixed research approach, and a sequential explanatory design—abdicative research strategy—a cross-sectional design one-time survey have been considered. Based on the model tested with SEM, AMOS, SPSS, and QDAML has been applied for data analysis. Result: The analysis of data, the survey results indicated that mobile banking services have significant positive effect on the performance of banks. This article finding has been useful in assisting banks in resolving issues related to Mobile banking services. The results of the survey showed that how much Ethiopian digital marketing services had progressed. It's similar, though, to toddlers who were going through a critical time and required round-the-clock care. Implication: The article suggests that bank executives should consider the needs for mobile marketing services from the viewpoint of consumers.